Energy and environmental issues for the practising architect a guide to help at the initial design stage - Ward, Ian C. (Thomas Telford, 2004)
Producing an energy-efficient, environmentally-friendly building can be a daunting task for the every day architect, who may only be commissioned infrequently to produce such a building. This title aims to remove the mystery and complexity from this process by helping the architect understand and put into practice the many issues.